KOMPETENSI MANAJERIAL DAN KETELADANAN PIMPINAN TERHADAP KINERJA GURU - S, Mathodah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Bad behavior and lack of achievement is one of failure characteristics in the implementation of education, and school in chief whom the n most blamed. Therefore, having a professional headmaster is important. This study aims to analyze the leadership of school headmaster on teacher performance. The research method uses quantitative, Pustek Vocational School is the object of research, teachers are research samples, research techniques use census sampling, questionnaires are research instruments, and analysis methods use regression. The results of the study show managerial competence and exemplary significant influence on teacher performance, both partially and simultaneously. This finding confirms that the leadership role in managing the organization cannot be ignored. it's important to have school headmaster whom has plenary abilities, both the ability to educate and manage the organization